Tire Sales Application Program At Lam Jaya Web-Based Store - Mar'atus Solikhah (Politeknik Siber Cerdika Internasional, 2020)
Along with the development of technology and information at this time, especially the world of computers is growing very rapidly, coupled with the presence of information technology that increasingly plays a role in the world of work. By using the right information technology tools, all human activities in the work can be done easily, efficiency and save time and cost, monitored and represented in accordance with the calculations and rules of the game that have been set. One of the information tools is the Internet, an unlimited global on-line network that provides millions of types of information. Internet is a connection facility of a website that wants to make itself as a social system that can be accepted by users and can be used as a positive thing Is a technique of collecting data, news, facts and information in the field that the process can be done by asking directly to the parties who can provide information about the problem that is being researched or indirectly such as making a phone call, emails and letters (written interviews).